10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Establishing direct breastfeeding in preterm infants remains challenging in neonatal intensive care units (NICUs). While cue-based feeding (CBF) is considered a developmentally supportive approach, its impact on direct breastfeeding remains uncertain. METHODS: We conducted a retrospective cohort study of preterm infants born at 27 + 0 to 33 + 6 weeks' gestation and admitted to a single tertiary NICU. Infants were assigned to two distinct study epochs reflecting different feeding approaches: traditional feeding (TF) and a breastfeeding-supportive CBF approach. A washout period was applied to minimize contamination between epochs. The primary outcome was direct breastfeeding at discharge (at least once daily). Secondary outcomes included PMA at discharge, length of hospitalization, and growth parameters. Multivariable logistic regression was used to evaluate factors associated with direct breastfeeding at discharge. RESULTS: A total of 135 preterm infants were included (CBF n = 66, TF n = 69). Direct breastfeeding at discharge was more frequent in the CBF group than in the TF group (48.5% versus 23.2%, p = 0.002). CBF was independently associated with any direct breastfeeding at discharge (odds ratio [OR] 5.09; 95% confidence interval [CI] 2.02-12.82), after adjustment for maternal age and mode of delivery. Infants in the CBF group were discharged at a lower PMA and had a shorter hospitalization. Weight and head circumference z-scores at discharge were similar between groups, despite greater declines in z-scores during hospitalization in the CBF group. CONCLUSIONS: In this cohort of preterm infants, implementation of a breastfeeding-supportive CBF approach was associated with higher rates of any direct breastfeeding at discharge and shorter length of hospitalization, without differences in weight or head circumference z-scores at discharge. These findings suggest that a breastfeeding-supportive CBF approach may facilitate the establishment of direct breastfeeding in the NICU.